Criminal Sanctions as the Answer of the Vaccum in Adminstrative Law Enforcement - Jennifer Jennifer; Anastasia Maria Gabriela; Kezia Linardi (Al-Bayyinah, 2022)
Administrative sanctions are considered not sufficient to meet the legal needs of state administration so that they require assistance with criminal sanctions in law enforcement. However, the clarity regarding the transition in the use of administrative sanctions to criminal sanctions has not been regulated with clear boundaries. The varied and subjective implementation certainly causes injustice and legal uncertainty for the community, especially those who receive sanctions. This study uses a juridical normative approach. This paper explains the role of criminal sanctions to fill the legal vacuum that cannot be provided by administrative sanctions, causing the importance of the existence of criminal sanctions in every administrative law. This paper also finds that there is no legal certainty to regulate the structure of the use of sanctions in administrative law. The urgency of the formation of rules that meet the structure, substance, and clear legal culture in its implementation will provide legal certainty and justice in the enforcement of state administrative law.